From tools to theories: The emergence of modern financial economics - Julia Koehn (Universität Witten/Herdecke, Fakultät für Wirtschaftswissenschaft, 2011)
It is shown that early research in modern financial economics had substantially been driven by the application of the research strategy of economics and the use of newly developed mathematical methods. For this purpose the professionalization of business education as a consequence of changes in the U.S. economy after Word War II is presented. The emergence of professional Journals in financial economics, similar to the academic culture including the trend of applying abstract mathematical reasoning and during the war developed methods like linear programming are highlighted. Also the meaning of Milton Friedman's 1953 essay The Methodology of Positive Economics for the dominance of abstract and prediction driven research in modern financial economics gets discussed. Finally, the emergence of Harry Markowitz's paper Portfolio Selection (1952) is used to substantiate the hypothesis.
Keywords: 330; history of finance; portfolio theory; business schools; modern financial economics; modelling; theories of modern financial economics; risk management; positivism; professionalization; methodology of finance